Switching from metal- to ligand-based oxidation in cobalt complexes with redox-active bisguanidine ligands - Lohmeyer, Lukas; Kaifer, Elisabeth; Enders, Markus; Himmel, Hans-Jörg (Chemistry - a European journal, 2021)
The control of the redox reactivity, magnetic and optical properties of the different redox states of complexes with redox-active ligands permits their rational use in catalysis and materials science. The redox-chemistry of octahedrally coordinated high-spin CoII complexes (three unpaired electrons) with one redox-active bisguanidine ligand and two acetylacetonato (acac) co-ligands is completely changed by replacing the acac by hexafluoro-acetylacetonato (hfacac) co-ligands. The first one-electron oxidation is metal-centered in the case of the complexes with acac co-ligands, giving diamagnetic CoIII complexes. By contrast, in the case of the less Lewis-basic hfacac co-ligands, the first one-electron oxidation becomes ligand-centered, leading to high-spin CoII complexes with a radical monocationic guanidine ligand unit (four unpaired electrons). Ferromagnetic coupling between the spins on the metal and the organic radical in solution is evidenced by temperature-dependent paramagnetic NMR studies, allowing to estimate the isotropic exchange coupling constant in solution. Second one-electron oxidation leads to high-spin CoII complexes with dicationic guanidine ligand units (three unpaired electrons) in the presence of hfacac co-ligands, but to low-spin CoIII complexes with radical monocationic, peralkylated guanidine ligand (one unpaired electron) in the presence of acac co-ligands. The analysis of the electronic structures is complemented by quantum-chemical calculations on the spin density distributions and relative energies of the possible redox isomers.